Factors Influencing Arms Proliferation on Rural Development in Katsina-Ala Local Government Area of Benue State, Nigeria - Agnes Olufunke Obademi; Jonathan Chagba; Omale Onuh (dialektika kontemporer, 2023)
The study investigated factors influencing arms proliferation and rural development in the Katsina-Ala Local Government Area of Benue State, Nigeria. The study was guided by two research questions, and a cross-sectional survey research design will be used to examine arms proliferation and criminality in Benue State. Area of the Study Katsina-Ala Local Government while the sample size for the study was 400, the research makes use of cluster and random sampling techniques to select the population of the study. By simple random sampling, the names of the ten (12) council wards were written on pieces of paper, wrapped, and dropped into a container and shaken thoroughly. Thereafter, five (6) council wards out of the original ten (12) wards were randomly selected. The data collected through the questionnaire was analysed using frequency counts and percentages. From the findings, it was concluded from the research findings that even though arms proliferation is caused by so many factors, profitability and utilisation of small arms have been singled out as the major cause of the unrest in Katsina-Ala Local Government Area of Benue State.